The effect of fathers' and mothers' educational level on adult oral health in Japan. Issue 3 (12th February 2016) - Murakami, Keiko; Kondo, Naoki; Ohkubo, Takayoshi; Hashimoto, Hideki
Abstract: Objectives: Previous studies have shown that childhood socioeconomic status is associated with oral health in adulthood, but these studies have not examined the effects of fathers' and mothers' characteristics separately. Our objective was to examine the effects of fathers' and mothers' educational level on oral health in adulthood. Methods: A questionnaire survey was conducted for community‐dwelling adults aged 25–50 years. A total of 4385 agreed to participate and complete the survey. Self‐rated oral health was used to evaluate current oral health. We conducted multiple logistic regression analyses to determine whether the fathers' or mothers' education was associated with current oral health after adjusting for the respondents' own education, current income, and childhood economic status. Results: Among respondents, 29.7% of men and 23.0% of women reported their own oral health as fair or poor. Among men, both the fathers' and mothers' education were significantly associated with oral health after adjusting for other socioeconomic indicators. After including the fathers' and mothers' education into the model simultaneously, a significant association remained only for the mothers' education; those whose mothers' educational attainment was junior high school had significantly higher odds ratio for poor oral health (1.90, 95% confidence interval 1.13–3.18) compared with those whose mothers' educational attainment was university or higher. Among women, neither the fathers' nor mothers' education was associated with oral health. Both childhood and current economic statuses were associated with oral health among women. Conclusions: Parental education was associated with adult oral health only among men. Among men, the association was stronger for the mothers' education than for the fathers' education. Further research should explore underlying mechanisms by which parental education, especially the mothers' education, affects their sons' oral health in later life.